Alleged cases of syphilis immortalized in the Krakow Altarpiece by Veit Stoss in the light of new research on the origins of the disease in Europe - Grzegorczyk, Wiesław; Grzegorczyk, Joanna; Grzegorczyk, Krzysztof (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
Syphilis is believed to occur in Europe as early as at the end of the fifteenth century when it was carried to Europe from America by Columbus’ sailors in 1493 (“Columbian” theory). In the nineteenth century this theory was questioned; reference was made to historical sources, pointing to the presence of syphilis in the Old World before Columbus (“pre-Columbian” theory). In 1933 a book was published by a Polish venereologist, professor Franciszek Walter on “dermatological details” of St. Mary’s Altar in Krakow by Veit Stoss. The author drew attention to the characters carved in the altar, which can show symptoms of late congenital syphilis (including saddle nose). Stoss’s work was completed in 1489, that is four years before the first Columbus expedition returned to Europe. If Walter’s hypothesis was true, syphilis would have existed in Europe before the discovery of America. In Krakow even older historical sights, mostly sculptures, can be found Prawwhich may suggest syphilis in the presented figures. Possible symptoms of syphilis seen in medieval works of art should be differentiated from other diseases, especially leprosy. Modern studies based on modern experimental methods (paleopathological, archaeological, phylogenetic) have not given yet definitive settlement of the dispute between supporters of two main theories of the origin of syphilis in Europe.

Już w końcu XV wieku uważano, że kiła przywleczona została do Europy z Ameryki przez marynarzy Kolumba w roku 1493 (teoria „kolumbijska”). W XIX wieku zaczęto kwestionować tę teorię; powoływano się na źródła historyczne, mające świadczyć o obecności kiły w Starym Świecie już przed Kolumbem (teoria „prekolumbijska”). W roku 1933 wydana została książka polskiego wenerologa, profesora Franciszka Waltera o „dermatologicznych szczegółach” ołtarza Wita Stwosza w krakowskim kościele Mariackim. Autor zwrócił w niej uwagę na uwiecznione w ołtarzu postacie, które wykazywać mogą objawy późnej kiły wrodzonej (m.in. nos siodełkowaty). Tymczasem dzieło Stwosza ukończone zostało w roku 1489 – cztery lata przed powrotem do Europy pierwszej wyprawy Kolumba. Jeśli hipoteza Waltera byłaby prawdziwa, kiła musiałaby istnieć w Europie przed odkryciem Ameryki. W Krakowie można wskazać zabytki jeszcze starsze, głównie rzeźbiarskie, mogące sugerować kiłę u przedstawionych postaci. Możliwe symptomy kiły widoczne w średniowiecznych dziełach sztuki należy różnicować z innymi chorobami, zwłaszcza trądem. Współczesne badania oparte o nowoczesne metody eksperymentalne (paleopatologiczne, archeologiczne, filogenetyczne) nie dały jak dotąd definitywnego rozstrzygnięcia sporu między zwolennikami obu głównych teorii pochodzenia kiły w Europie.
Domniemane przypadki kiły uwiecznione w krakowskim ołtarzu Wita Stwosza w świetle nowych badań nad początkami tej choroby w Europie
Keywords: history of medicine; Franciszek Walter; art; syphilis; historia medycyny; sztuka; kiła